Resin composition, resin molded article, and method for manufacturing plated resin molded article

By blending polyolefin with thermoplastic resins and LDS additives, the resin composition addresses the challenge of high dielectricity in LDS technology, enabling low-dielectric and platable resin molded products.

JP7627162B2Active Publication Date: 2025-02-05MITSUBISHI ENG PLASTICS CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021062008
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-02-05
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Existing resin compositions used in laser direct structuring (LDS) technology do not effectively reduce dielectric characteristics, hindering the formation of low-dielectric resin compositions and plated resin molded products.

Method used

A resin composition is formulated by blending polyolefin with thermoplastic resins such as polycarbonate, polyphenylene ether, polyester, and polyamide resins, along with LDS additives, at specific ratios to achieve low dielectric properties while maintaining plating capabilities.

Benefits of technology

The composition achieves low dielectric characteristics and enables effective plating on resin molded products, enhancing their performance for applications like antennas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627162000007
    Figure 0007627162000007
  • Figure 0007627162000001
    Figure 0007627162000001
  • Figure 0007627162000002
    Figure 0007627162000002
Patent Text Reader

Abstract

To provide a resin composition, a resin molding and a method for manufacturing a plated resin molding which can provide a resin molding that can be plated and has low dielectric property.SOLUTION: A resin composition for low dielectric laser direct structuring contains a thermoplastic resin, a laser direct structuring additive, and polyolefin, where the thermoplastic resin contains at least one of a polycarbonate resin, a polyphenylene ether resin, a polyester resin and a polyamide resin, and contains 4.0-30.0 pts.mass of polyolefin with respect to 100 pts.mass of the thermoplastic resin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a resin molded article, and a method for producing a plated resin molded article. [Background technology]

[0002] In recent years, with the development of mobile phones including smartphones, various methods for manufacturing antennas inside mobile phones have been considered. In particular, there is a demand for a method for manufacturing an antenna that can be designed three-dimensionally for a mobile phone. As one of the techniques for forming such a three-dimensional antenna, laser direct structuring (hereinafter sometimes referred to as "LDS") technology has attracted attention. The LDS technology is, for example, a technology for irradiating a laser onto the surface of a resin molded product containing an LDS additive to activate it, and applying a metal to the activated part to form a plating. The feature of this technology is that it is possible to manufacture a metal structure such as an antenna directly on the surface of a resin molded product without using an adhesive or the like. Such LDS technology is disclosed, for example, in Patent Documents 1 to 3. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-144767 A [Patent Document 2] JP 2014-043549 A [Patent Document 3] International Publication No. 2017 / 102930 Summary of the Invention [Problem to be solved by the invention]

[0004] Here, as the use of LDS technology spreads, there is also a demand for resin compositions for LDS with low dielectric properties. In order to reduce the dielectric constant of a resin composition, it is possible to alloy a resin with relatively low dielectric properties with a thermoplastic resin. However, the present inventors conducted research and found that in resin compositions containing LDS additives, the relative dielectric constant or dielectric loss tangent may not decrease even if a resin with low dielectric properties is alloyed. The present invention aims to solve these problems, and to provide a resin composition, a resin molded article, and a method for producing a plated resin molded article, which are capable of forming a plating and providing a low-dielectric resin molded article. [Means for solving the problem]

[0005] In view of the above-mentioned problems, the present inventors have conducted research and found that the above-mentioned problems can be solved by blending a polyolefin in a specified ratio together with an LDS additive to a specified thermoplastic resin. Specifically, the above-mentioned problems have been solved by the following means. <1> A low dielectric resin composition for laser direct structuring, comprising a thermoplastic resin, a laser direct structuring additive, and a polyolefin, wherein the thermoplastic resin comprises at least one of a polycarbonate resin, a polyphenylene ether resin, a polyester resin, and a polyamide resin, and the polyolefin is contained in an amount of 4.0 to 30.0 parts by mass per 100 parts by mass of the thermoplastic resin. <2> The thermoplastic resin comprises a polyamide resin. <1> The resin composition according to claim 1. <3> The polyamide resin comprises a semi-aromatic polyamide resin. <2> The resin composition according to claim 1. <4> At least one of the polyamide resins contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 70 mol % or more of the diamine-derived structural units are derived from xylylenediamine, and 70 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. <2> The resin composition according to claim 1. <5> The laser direct structuring additive is contained in an amount of 1.0 to 30.0 parts by mass relative to 100 parts by mass of the thermoplastic resin. <1> ~ <4> 10. The resin composition according to claim 9 . <6> The laser direct structuring additive comprises at least one of copper, antimony, tin, aluminum and zinc; <1> ~ <5> 10. The resin composition according to claim 9 . <7> The laser direct structuring additive comprises copper chromium oxide and / or an oxide containing antimony and tin; <1> ~ <5> 10. The resin composition according to claim 9 . <8> The resistivity of the laser direct structuring additive is 5×10 3 More than Ω·cm <1> ~ <7> 10. The resin composition according to claim 9 . <9> The polyolefin includes an acid-modified polyolefin. <1> ~ <8> 10. The resin composition according to claim 9 . <10> The polyolefin comprises polyethylene. <1> ~ <9> 10. The resin composition according to claim 9 . <11> Further, the composition contains 10.0 to 150.0 parts by mass of inorganic fibers relative to 100 parts by mass of the thermoplastic resin. <1> ~ <10> 10. The resin composition according to claim 9 . <12> The inorganic fiber has a relative dielectric constant of 7 or less. <11> The resin composition according to claim 1. <13> The inorganic fibers include glass fibers. <11> or <12> The resin composition according to claim 1. <14> The glass fiber is composed of 65 to 85 mass% of SiO2, 15 to 30 mass% of B2O3, 0 to 4 mass% of sodium oxide (Na2O) and / or potassium oxide (K2O), and 0 to 4 mass% of other components. <13> The resin composition according to claim 1. <15> The inorganic fibers are contained in an amount of 20.0 to 80.0 parts by mass relative to 100 parts by mass of the thermoplastic resin. <11> ~ <14> 10. The resin composition according to claim 9 . <16> Further, talc is contained in an amount of 0.1 to 200.0 parts by mass per 100.0 parts by mass of the laser direct structuring additive. <1> ~ <15> 10. The resin composition according to claim 9 . <17> The resin composition has a relative dielectric constant of 3.60 or less at a frequency of 2.45 GHz. <1> ~ <16> 10. The resin composition according to claim 9 . <18> <1> ~ <17> 2. A resin molded product formed from the resin composition according to claim 1. <19> The resin molded product has a plating on its surface. <18> 2. The resin molded product according to claim 1 . <20> The plating has antenna properties. <19> 2. The resin molded product according to claim 1 . <21> Parts for portable electronic devices, <18> ~ <20> 10. The resin molded product according to claim 9, <22> <1> ~ <17> irradiating a surface of a resin molded article formed from the resin composition according to any one of claims 1 to 5 with a laser, and then applying a metal to form a plating. Effect of the Invention

[0006] According to the present invention, it is possible to provide a resin composition, a resin molded article, and a method for producing a plated resin molded article, which are capable of forming a plating and providing a low-dielectric resin molded article. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a schematic diagram showing a process of plating the surface of a resin molded product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, the number average molecular weight is a polystyrene equivalent value measured by GPC (gel permeation chromatography). In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified. In cases where the standards shown in this specification differ depending on the year and the measurement method, etc., they shall be based on the standards as of January 1, 2021, unless otherwise stated.

[0009] The resin composition of the present embodiment contains a thermoplastic resin, a laser direct structuring additive, and a polyolefin, the thermoplastic resin containing at least one of a polycarbonate resin, a polyphenylene ether resin, a polyester resin, and a polyamide resin, and the resin composition contains 4.0 to 30.0 parts by mass of the polyolefin per 100 parts by mass of the thermoplastic resin, has low dielectric properties, and is used for laser direct structuring. By blending a polyolefin and an LDS additive with at least one thermoplastic resin selected from the group consisting of polycarbonate resin, polyphenylene ether resin, polyester resin, and polyamide resin, it is possible to lower the dielectric properties of the resin composition while maintaining the plating properties of a resin molded product obtained from the resin composition. It was thought that the dielectric properties of a resin composition could be lowered by blending a resin with relatively low dielectric properties with a thermoplastic resin. However, for example, when polyphenylene sulfide was blended with a polyamide resin, the dielectric tangent of the resin composition could be slightly lowered, but the relative dielectric constant remained almost unchanged, and plating could not be formed. Then, the inventors conducted research and found that by using a polyolefin as a resin for lowering the dielectric properties of a thermoplastic resin, it was possible to sufficiently lower the dielectric properties while maintaining plating properties.

[0010] <Thermoplastic resin> The resin composition of the present embodiment contains at least one of a polycarbonate resin, a polyphenylene ether resin, a polyester resin, and a polyamide resin as a thermoplastic resin, and preferably contains a polyamide resin. By combining such a thermoplastic resin with a polyolefin, it becomes possible to form a plating on the obtained resin molded product while sufficiently reducing the dielectric properties.

[0011] In the present embodiment, a preferred example of the thermoplastic resin contains a polycarbonate resin, and 90% by mass or more (preferably 95% by mass or more) of the resin composition is a polycarbonate resin. Another preferred example of the thermoplastic resin in this embodiment is one that contains a polyphenylene ether resin, and 90 mass % or more (preferably 95 mass % or more) of the thermoplastic resin contained in the resin composition is a polyphenylene ether resin. Another preferred example of the thermoplastic resin in this embodiment is one that contains a polyester resin (preferably, polybutylene terephthalate resin), and 90 mass % or more (preferably 95 mass % or more) of the thermoplastic resin contained in the resin composition is a polyester resin (preferably, polybutylene terephthalate resin). Another preferred example of the thermoplastic resin in this embodiment is one that contains a polyamide resin (preferably, a xylylenediamine-based polyamide resin described below), and 90 mass % or more (preferably, 95 mass % or more) of the thermoplastic resin contained in the resin composition is a polyamide resin (preferably, a xylylenediamine-based polyamide resin described below).

[0012] <<Polycarbonate resin>> The polycarbonate resin is not particularly limited, and any of aromatic polycarbonate resin, aliphatic polycarbonate resin, and aromatic-aliphatic polycarbonate resin can be used. Among them, aromatic polycarbonate resin is preferable, and aromatic polycarbonate resin obtained by reacting aromatic dihydroxy compound with phosgene or carbonic acid diester is more preferable, bisphenol A type polycarbonate resin and / or bisphenol C type polycarbonate resin is preferable, and blend of bisphenol A type polycarbonate resin and bisphenol C type polycarbonate resin is more preferable.

[0013] Examples of aromatic dihydroxy compounds include 2,2-bis(4-hydroxyphenyl)propane (=bisphenol A), tetramethylbisphenol A, bis(4-hydroxyphenyl)-p-diisopropylbenzene, hydroquinone, resorcinol, and 4,4-dihydroxydiphenyl, and preferably bisphenol A. Furthermore, for the purpose of preparing a resin composition having high flame retardancy, a compound in which one or more tetraalkylphosphonium sulfonates are bonded to the aromatic dihydroxy compounds, or a polymer or oligomer having a siloxane structure and containing phenolic OH groups at both ends can be used.

[0014] The method for producing the polycarbonate resin is not particularly limited, and in this embodiment, polycarbonate resins produced by any method such as the phosgene method (interfacial polymerization method) and the melting method (ester exchange method) can be used. In addition, in this embodiment, polycarbonate resins produced by a process of adjusting the amount of OH groups in the terminal groups after a general melting method production process may be used.

[0015] Furthermore, the polycarbonate resin used in the present embodiment may be not only a polycarbonate resin as a virgin raw material, but also a polycarbonate resin regenerated from used products, that is, a so-called material recycled polycarbonate resin.

[0016] The molecular weight of the polycarbonate resin that can be used in the present embodiment is preferably 10,000 or more, more preferably 15,000 or more, as calculated from the solution viscosity measured at 25° C. using methylene chloride as a solvent. The viscosity average molecular weight is preferably 32,000 or less, more preferably 28,000 or less. By setting the viscosity average molecular weight to be equal to or more than the lower limit, the mechanical properties of the molded product tend to be improved, and by setting the viscosity average molecular weight to be equal to or less than the upper limit, the processability during injection molding tends to be improved. Two or more polycarbonate resins having different viscosity average molecular weights may be mixed and used. In this case, polycarbonates having a viscosity average molecular weight outside the above-mentioned preferred range may be mixed. Here, the viscosity average molecular weight [Mv] is calculated by using methylene chloride as a solvent, measuring the intrinsic viscosity [η] (unit: dL / g) at 25°C using an Ubbelohde viscometer, and calculating the viscosity average molecular weight according to the Schnell viscosity formula, i.e., η = 1.23 × 10 -4 Mv 0.83 The intrinsic viscosity [η] is the value calculated from the specific viscosity [η sp ] was measured and the value was calculated according to the following formula.

number

[0017] For further information regarding the polycarbonate resin used in this embodiment, reference can be made to, for example, the descriptions in paragraphs 0018 to 0066 of JP 2012-072338 A and paragraphs 0011 to 0018 of JP 2015-166460 A, the contents of which are incorporated herein by reference.

[0018] <<Polyphenylene ether resin>> In this embodiment, a known polyphenylene ether resin can be used, for example, a polymer having a structural unit represented by the following formula in the main chain (preferably a polymer in which the structural unit represented by the following formula accounts for 90 mol % or more of all structural units excluding terminal groups). The polyphenylene ether resin may be either a homopolymer or a copolymer.

[0019] [ka] (Wherein, two R a each independently represents a hydrogen atom, a halogen atom, a primary or secondary alkyl group, an aryl group, an aminoalkyl group, a halogenated alkyl group, a hydrocarbyloxy group, or a halogenated hydrocarbyloxy group; b each independently represents a hydrogen atom, a halogen atom, a primary or secondary alkyl group, an aryl group, a halogenated alkyl group, a hydrocarbyloxy group, or a halogenated hydrocarbyloxy group. a cannot both become hydrogen atoms.)

[0020] R a and R b are each independently preferably a hydrogen atom, a primary or secondary alkyl group, or an aryl group. Suitable examples of the primary alkyl group include a methyl group, an ethyl group, an n-propyl group, an n-butyl group, an n-amyl group, an isoamyl group, a 2-methylbutyl group, a 2,3-dimethylbutyl group, a 2-, 3-, or 4-methylpentyl group, or a heptyl group. Suitable examples of the secondary alkyl group include an isopropyl group, a sec-butyl group, or a 1-ethylpropyl group. In particular, R a R is preferably a primary or secondary alkyl group having 1 to 4 carbon atoms or a phenyl group. b is preferably a hydrogen atom.

[0021] Suitable homopolymers of polyphenylene ether resins include, for example, polymers of 2,6-dialkylphenylene ethers such as poly(2,6-dimethyl-1,4-phenylene) ether, poly(2,6-diethyl-1,4-phenylene ether), poly(2,6-dipropyl-1,4-phenylene ether), poly(2-ethyl-6-methyl-1,4-phenylene ether), and poly(2-methyl-6-propyl-1,4-phenylene ether). Examples of the copolymer include 2,6-dialkylphenol / 2,3,6-trialkylphenol copolymers such as 2,6-dimethylphenol / 2,3,6-trimethylphenol copolymer, 2,6-dimethylphenol / 2,3,6-triethylphenol copolymer, 2,6-diethylphenol / 2,3,6-trimethylphenol copolymer, and 2,6-dipropylphenol / 2,3,6-trimethylphenol copolymer; graft copolymers obtained by graft polymerizing styrene onto poly(2,6-dimethyl-1,4-phenylene ether); and graft copolymers obtained by graft polymerizing styrene onto a 2,6-dimethylphenol / 2,3,6-trimethylphenol copolymer.

[0022] In the present embodiment, the polyphenylene ether resin is preferably poly(2,6-dimethyl-1,4-phenylene) ether or a 2,6-dimethylphenol / 2,3,6-trimethylphenol random copolymer. In addition, a polyphenylene ether resin having a specified number of terminal groups and copper content as described in JP-A-2005-344065 can also be suitably used.

[0023] The polyphenylene ether resin preferably has an intrinsic viscosity of 0.2 to 0.8 dL / g, more preferably 0.3 to 0.6 dL / g, measured in chloroform at 30°C. By making the intrinsic viscosity 0.2 dL / g or more, the mechanical strength of the resin composition tends to be improved, and by making it 0.8 dL / g or less, the fluidity tends to be improved and molding processing tends to be easier. In addition, two or more polyphenylene ether resins having different intrinsic viscosities may be used in combination to achieve this intrinsic viscosity range.

[0024] The method for producing the polyphenylene ether resin used in the present embodiment is not particularly limited, and may be, for example, a method of oxidatively polymerizing a monomer such as 2,6-dimethylphenol in the presence of an amine copper catalyst according to a known method, in which the intrinsic viscosity can be controlled within a desired range by selecting reaction conditions. The intrinsic viscosity can be controlled by selecting conditions such as polymerization temperature, polymerization time, and catalyst amount.

[0025] <<Polyester resin>> As the polyester resin, a known thermoplastic polyester resin can be used, and it is preferable that the polyester resin contains a polyethylene terephthalate resin and / or a polybutylene terephthalate resin, and it is more preferable that the polyester resin contains at least a polybutylene terephthalate resin. As is well known, polyethylene terephthalate resins and polybutylene terephthalate resins are produced on a large scale by reacting terephthalic acid or ester with ethylene glycol or 1,4-butanediol, and are distributed on the market. In this embodiment, these resins available on the market can be used. Some of the resins available on the market contain copolymer components other than the terephthalic acid component and the ethylene glycol component or 1,4-butanediol component, but in this embodiment, those containing the copolymer components preferably in an amount of 3 to 40 mass%, more preferably 5 to 30 mass%, and even more preferably 10 to 25 mass% can also be used.

[0026] The intrinsic viscosity of the polyethylene terephthalate resin is usually 0.4 to 1.0 dL / g, and preferably 0.5 to 1.0 dL / g. When the intrinsic viscosity is equal to or higher than the lower limit, the mechanical properties of the resin composition are less likely to deteriorate, and when the intrinsic viscosity is equal to or lower than the upper limit, the fluidity is easily maintained. The intrinsic viscosity of the polybutylene terephthalate resin is usually 0.5 to 1.5 dL / g, and preferably 0.6 to 1.3 dL / g. If it is equal to or higher than the lower limit, it is easy to obtain a resin composition having excellent mechanical strength. If it is equal to or lower than the upper limit, the flowability of the resin composition is not lost, and the moldability tends to be excellent. The intrinsic viscosity of each polyester resin was measured at 30° C. in a mixed solvent of phenol / tetrachloroethane (mass ratio 1 / 1). The amount of terminal carboxyl groups in the polyester resin (preferably polybutylene terephthalate resin) is usually 60 eq / ton or less, preferably 50 eq / ton or less, and preferably 30 eq / ton or less. By making it 60 eq / ton or more, the alkali resistance and hydrolysis resistance are improved, and gas is less likely to be generated during melt molding of the resin composition. The lower limit of the amount of terminal carboxyl groups is not particularly set, but is usually 10 eq / ton in consideration of the productivity of the production of the polyester resin. The amount of terminal carboxyl groups in the polyester resin can be determined by dissolving 0.5 g of the resin in 25 mL of benzyl alcohol and titrating the resultant solution with a 0.01 mol / L benzyl alcohol solution of sodium hydroxide.

[0027] The polybutylene terephthalate resin may be a polybutylene terephthalate resin modified by copolymerization, and specific preferred copolymers thereof include polyester ether resins copolymerized with polyalkylene glycols, particularly polytetramethylene glycol, dimer acid copolymerized polybutylene terephthalate resins, and isophthalic acid copolymerized polybutylene terephthalate resins. These copolymers refer to those in which the copolymerization amount is 1 mol% or more and less than 50 mol% of the total polybutylene terephthalate resin segments. Among these, the copolymerization amount is preferably 2 to 50 mol%, more preferably 3 to 40 mol%, and particularly preferably 5 to 20 mol%. For details of these, reference can be made to paragraphs 0014 to 0022 of JP 2019-006866 A, the contents of which are incorporated herein by reference.

[0028] In addition to the above, the polyester resin may be described in paragraphs 0013 to 0016 of JP-A-2010-174223, the contents of which are incorporated herein by reference.

[0029] <<Polyamide resin>> The type of polyamide resin used in the present embodiment is not particularly limited, and may be an aliphatic polyamide resin or a semi-aromatic polyamide resin. For the polyamide resin, for example, the description in paragraphs 0011 to 0013 of JP 2011-132550 A can be referred to, and the contents thereof are incorporated herein. The polyamide resin used in this embodiment preferably contains a semi-aromatic polyamide resin. For example, it is more preferable that 90% by mass or more of the polyamide resin contained in the resin composition of this embodiment is a semi-aromatic polyamide resin. Here, the semi-aromatic polyamide resin is composed of a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 20 to 80 mol% of the total structural units of the diamine-derived structural unit and the dicarboxylic acid-derived structural unit are structural units containing an aromatic ring. By using such a semi-aromatic polyamide resin, the mechanical strength of the obtained resin molded product can be increased. Examples of the semi-aromatic polyamide resin include terephthalic acid-based polyamide resin (polyamide 6T, polyamide 9T, polyamide 10T) and the xylylenediamine-based polyamide resin described later.

[0030] At least one of the polyamide resins used in the present embodiment contains diamine-derived structural units and dicarboxylic acid-derived structural units, and it is preferred that 70 mol % or more of the diamine-derived structural units are derived from xylylenediamine, and 70 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. Hereinafter, such a polyamide resin may be referred to as a xylylenediamine-based polyamide resin. The diamine-derived constituent units of the xylylenediamine-based polyamide resin are more preferably 75 mol% or more, even more preferably 80 mol% or more, even more preferably 85 mol% or more, still more preferably 90 mol% or more, and even more preferably 95 mol% or more derived from xylylenediamine. The dicarboxylic acid-derived constituent units of the xylylenediamine-based polyamide resin are more preferably 75 mol% or more, even more preferably 80 mol% or more, even more preferably 90 mol% or more, and even more preferably 95 mol% or more derived from α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms.

[0031] Diamines other than metaxylylenediamine and paraxylylenediamine that can be used as the raw diamine component of the xylylenediamine-based polyamide resin include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine, 1,3-bis( Examples of the diamines include alicyclic diamines such as bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane; and diamines having an aromatic ring such as bis(4-aminophenyl)ether, paraphenylenediamine, and bis(aminomethyl)naphthalene. These can be used alone or in combination of two or more.

[0032] Examples of α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms that are suitable for use as the raw dicarboxylic acid component of the xylylenediamine-based polyamide resin include aliphatic dicarboxylic acids such as succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, adipic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid. One or a mixture of two or more of these can be used. Among these, adipic acid or sebacic acid are more preferred, and sebacic acid is even more preferred, since the melting point of the polyamide resin falls within a range suitable for molding.

[0033] Examples of dicarboxylic acid components other than the above-mentioned α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms include phthalic acid compounds such as isophthalic acid, terephthalic acid, and orthophthalic acid, and isomers of naphthalenedicarboxylic acids such as 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid. These can be used alone or in combination of two or more kinds.

[0034] In the xylylenediamine-based polyamide resin of the present embodiment, 0 to 100 mol % of the diamine-derived structural units are derived from paraxylylenediamine, 100 to 0 mol % are derived from metaxylylenediamine, and 70 mol % or more (preferably 80 mol % or more, more preferably 90 mol % or more) of the dicarboxylic acid-derived structural units are derived from sebacic acid and / or adipic acid. An example of a more preferred embodiment A of the xylylenediamine-based polyamide resin is one in which 70 mol % or more (preferably 80 mol % or more, more preferably 90 mol % or more, and even more preferably 95 mol % or more) of the diamine-derived structural units are derived from paraxylylenediamine, and 70 mol % or more (preferably 80 mol % or more, and more preferably 90 mol % or more) of the dicarboxylic acid-derived structural units are derived from sebacic acid. Furthermore, a more preferred embodiment B of the xylylenediamine-based polyamide resin is, for example, a polyamide resin in which 30 to 90 mol % (preferably 60 to 80 mol %) of the diamine-derived structural units are derived from meta-xylylenediamine, 70 to 10 mol % (preferably 40 to 20 mol %) are derived from para-xylylenediamine, and 70 mol % or more (preferably 80 mol % or more, more preferably 90 mol % or more) of the dicarboxylic acid-derived structural units are derived from sebacic acid. An example of a more preferred embodiment C of the xylylenediamine-based polyamide resin is one in which 70 mol % or more (preferably 80 mol % or more, more preferably 90 mol % or more, and even more preferably 95 mol % or more) of the diamine-derived structural units are derived from metaxylylenediamine, and 70 mol % or more (preferably 80 mol % or more, and more preferably 90 mol % or more) of the dicarboxylic acid-derived structural units are derived from adipic acid. In the resin composition of this embodiment, embodiment A is particularly preferred. In any of the above embodiments, the total amount of constitutional units derived from diamines does not exceed 100 mol %, and the total amount of constitutional units derived from dicarboxylic acids does not exceed 100 mol %.

[0035] Although the diamine-derived structural unit and the dicarboxylic acid-derived structural unit are the main components, other structural units are not completely excluded, and it goes without saying that the resin may contain lactams such as ε-caprolactam and laurolactam, and aliphatic aminocarboxylic acid-derived structural units such as aminocaproic acid and aminoundecanoic acid. Here, the main component means that the total number of the diamine-derived structural unit and the dicarboxylic acid-derived structural unit is the largest among all the structural units constituting the xylylenediamine-based polyamide resin. In this embodiment, the total of the diamine-derived structural unit and the dicarboxylic acid-derived structural unit in the xylylenediamine-based polyamide resin preferably accounts for 90% or more of the total structural units, more preferably accounts for 95% or more, and even more preferably accounts for 98% or more.

[0036] The melting point of the polyamide resin is preferably from 150 to 350°C, more preferably from 180 to 330°C, and further preferably from 200 to 300°C. The melting point can be measured by differential scanning calorimetry in accordance with JIS K7121 and K7122.

[0037] The lower limit of the number average molecular weight (Mn) of the polyamide resin is preferably 6,000 or more, more preferably 8,000 or more, even more preferably 10,000 or more, even more preferably 15,000 or more, even more preferably 20,000 or more, and even more preferably 22,000 or more. The upper limit of the Mn is preferably 35,000 or less, more preferably 30,000 or less, even more preferably 28,000 or less, and even more preferably 26,000 or less. Within such a range, the heat resistance, elastic modulus, dimensional stability, and moldability are improved.

[0038] The content of the thermoplastic resin in the resin composition of the present embodiment is preferably 30% by mass or more, more preferably 35% by mass or more, even more preferably 40% by mass or more, and even more preferably 45% by mass or more. By making it equal to or more than the lower limit, the mechanical strength of the molded article tends to be improved. The content of the thermoplastic resin in the resin composition of the present embodiment is preferably 80% by mass or less, more preferably 75% by mass or less, and even more preferably 70% by mass or less. By making it equal to or less than the upper limit, the mechanical strength of the molded article tends to be maintained. The resin composition of the present embodiment may contain only one type of each thermoplastic resin, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0039] <Laser direct structuring additive> The resin composition of the present embodiment contains a laser direct structuring additive (LDS additive). By containing the LDS additive, it becomes possible to form plating on the obtained resin molded article. The LDS additive in this embodiment refers to a compound that can selectively form plating only in the laser irradiated area when 10 parts by mass of an additive considered to be an LDS additive is added to 100 parts by mass of any of polycarbonate resin, polyphenylene ether resin, polyester resin, and polyamide resin, and the resulting material is irradiated with a YAG laser having a wavelength of 1064 nm at an output of 10 W, a frequency of 80 kHz, and a speed of 3 m / s, and then immersed in an electroless plating bath as a plating process. The LDS additive used in this embodiment may be a synthetic product or a commercially available product. In addition to commercially available products as LDS additives, commercially available products may be substances sold for other purposes as long as they satisfy the requirements of the LDS additive in this embodiment. Only one type of LDS additive may be used, or two or more types may be used in combination.

[0040] The LDS additive used in the present embodiment preferably contains at least one of copper, antimony, tin, aluminum, and zinc, more preferably contains copper chromium copper oxide and / or an oxide containing antimony and tin, and even more preferably contains copper chromium copper oxide. In addition, the LDS additive used in this embodiment has a resistivity of 5×10 3 It is preferable that the resistivity is more than Ω·cm. By using an LDS additive with such a high resistivity, it is possible to obtain a resin composition with lower dielectric properties.

[0041] More specifically, a first embodiment of the LDS additive used in this embodiment is a compound containing copper and chromium. The LDS additive of the first embodiment preferably contains 10 to 30 mass% copper. Also, it preferably contains 15 to 50 mass% chromium. The LDS additive of the first embodiment is preferably an oxide containing copper and chromium (copper chromium oxide).

[0042] The preferred form of copper and chromium inclusion is a spinel structure, which is one of the typical crystal structures found in AB2O4 type compounds (A and B are metal elements) in double oxides.

[0043] The LDS additive of the first embodiment may contain trace amounts of other metals in addition to copper and chromium. Examples of other metals include antimony, tin, lead, indium, iron, cobalt, nickel, zinc, cadmium, silver, bismuth, arsenic, manganese, magnesium, and calcium, with manganese being preferred. These metals may be present as oxides. A preferred example of the LDS additive of the first embodiment is an LDS additive having a content of metal oxides other than copper chromium oxide of 10 mass % or less.

[0044] A second embodiment of the LDS additive used in this embodiment is an oxide containing at least one of antimony and phosphorus, and tin, preferably an oxide containing antimony and tin.

[0045] The LDS additive of the second embodiment preferably has a tin content greater than the phosphorus and antimony contents, and more preferably the amount of tin relative to the total amount of tin, phosphorus and antimony is 80 mass % or more.

[0046] In particular, as the LDS additive of the second embodiment, an oxide containing antimony and tin is preferable, an oxide in which the tin content is greater than the antimony content is more preferable, and an oxide in which the amount of tin relative to the total amount of tin and antimony is 80 mass% or more is even more preferable. More specifically, examples of the LDS additive of the second embodiment include antimony-doped tin oxide, antimony oxide-doped tin oxide, phosphorus-doped tin oxide, and phosphorus oxide-doped tin oxide, with antimony oxide-doped tin oxide and antimony oxide-doped tin oxide being preferred, and antimony oxide-doped tin oxide being more preferred.

[0047] The number average particle size of the LDS additive used in this embodiment is preferably 0.01 to 100 μm, more preferably 0.05 to 30 μm, and even more preferably 0.05 to 15 μm. By setting the number average particle size in this range, the plating surface can be made more uniform.

[0048] The content of the LDS additive in the resin composition of this embodiment is preferably 1.0 part by mass or more, more preferably 2.0 parts by mass or more, even more preferably 3.0 parts by mass or more, even more preferably 4.0 parts by mass or more, and even more preferably 5.0 parts by mass or more, relative to 100 parts by mass of the thermoplastic resin. By making it equal to or more than the lower limit, plating property tends to be further improved. In addition, the content of the LDS additive in the resin composition of this embodiment is preferably 30.0 parts by mass or less, more preferably 25.0 parts by mass or less, even more preferably 20.0 parts by mass or less, even more preferably 15.0 parts by mass or less, and even more preferably 10.0 parts by mass or less, relative to 100 parts by mass of the thermoplastic resin. By making it equal to or less than the upper limit, the resin composition tends to exhibit lower dielectric constant. The resin composition of the present embodiment may contain only one type of LDS additive, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0049] <Polyolefin> The resin composition of the present embodiment contains 4.0 to 30.0 parts by mass of polyolefin per 100 parts by mass of thermoplastic resin. By containing polyolefin, it is possible to impart plating properties to the obtained resin molded article and to reduce dielectric constant. As the polyolefin, a homopolymer and / or copolymer of an α-olefin such as ethylene, propylene, or butene is preferred.

[0050] As homopolymers, polyethylene and polypropylene are preferred, with polyethylene being more preferred. On the other hand, as the copolymer, a polymer of at least two of ethylene, propylene, and butene, or a copolymer of at least one of ethylene, propylene, and butene with a monomer that can be copolymerized therewith can be used. Examples of the monomer that can be copolymerized with at least one of ethylene, propylene, and butene include α-olefins, styrenes, dienes, cyclic compounds, and oxygen atom-containing compounds. Particularly preferred copolymers include ethylene / butene copolymers and ethylene / propylene copolymers, with ethylene / butene copolymers being preferred. For details of α-olefins, styrenes, dienes, cyclic compounds, and oxygen-containing compounds, please refer to paragraph 0044 of WO 2017 / 094564, the contents of which are incorporated herein by reference. The copolymer may be any of an alternating copolymer, a random copolymer, and a block copolymer.

[0051] As the polyethylene, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), very low density polyethylene (VLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), etc. can be used, with HDPE being preferred.

[0052] In this embodiment, the polyolefin is preferably an acid-modified polyolefin. The acid-modified polyolefin is preferably a polyolefin acid-modified with a carboxylic acid and / or a derivative thereof, or a polyolefin acid-modified with a carboxylic acid and / or a derivative thereof and further grafted with a polyamide via a functional group introduced into the molecule by the acid modification. By using an acid-modified polyolefin, a functional group having affinity for a thermoplastic resin can be introduced into the molecule, and the dispersibility of the polyolefin in the thermoplastic resin tends to be further improved. This is particularly effective when a polyamide resin is used as the thermoplastic resin.

[0053] Examples of compounds capable of acid-modifying polyolefins include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, methylmaleic acid, methylfumaric acid, mesaconic acid, citraconic acid, glutaconic acid, cis-4-cyclohexene-1,2-dicarboxylic acid, endo-bicyclo[2.2.1]-5-heptene-2,3-dicarboxylic acid, and metal salts of these carboxylic acids, monomethyl maleate, monomethyl itaconate, methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, and methyl methacrylate. Preferred examples of the above include 2-ethylhexyl methacrylate, hydroxyethyl methacrylate, aminoethyl methacrylate, dimethyl maleate, dimethyl itaconate, maleic anhydride, itaconic anhydride, citraconic anhydride, endobicyclo-[2.2.1]-5-heptene-2,3-dicarboxylic anhydride, maleimide, N-ethylmaleimide, N-butylmaleimide, N-phenylmaleimide, acrylamide, methacrylamide, glycidyl acrylate, glycidyl methacrylate, glycidyl ethacrylate, glycidyl itaconate, and glycidyl citraconate. These can be used alone or in combination of two or more. Among these, maleic anhydride is preferred from the viewpoint of melt mixability with other resins.

[0054] In the present embodiment, examples of acid-modified polyolefins that are particularly preferably used include maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, and maleic anhydride-modified ethylene / butene copolymers from the viewpoints of elastic modulus, flexibility, and impact resistance. Among these, maleic anhydride-modified polyethylene and maleic anhydride-modified polypropylene are particularly preferably used.

[0055] For other details about polyolefins, reference can be made to paragraphs 0042 to 0056 of WO 2017 / 094564, the contents of which are incorporated herein by reference.

[0056] The content of the polyolefin in the resin composition of this embodiment is 4.0 parts by mass or more, preferably 6.0 parts by mass or more, more preferably 8.0 parts by mass or more, even more preferably 10.0 parts by mass or more, even more preferably 12.0 parts by mass or more, and even more preferably 14.0 parts by mass or more, relative to 100 parts by mass of the thermoplastic resin. By making it equal to or more than the lower limit, the dielectric properties of the resin composition tend to be lowered. In addition, the content of the polyolefin in the resin composition of this embodiment is 30.0 parts by mass or less, preferably 28.0 parts by mass or less, even more preferably 26.0 parts by mass or less, even more preferably 24.0 parts by mass or less, and even more preferably 22.0 parts by mass or less, relative to 100 parts by mass of the thermoplastic resin. By making it equal to or less than the upper limit, it is possible to suppress a significant decrease in the inherent mechanical properties and thermal properties of the thermoplastic resin. The resin composition of the present embodiment may contain only one type of polyolefin, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0057] In the resin composition of this embodiment, the mass ratio of polyolefin to LDS additive (LDS / polyolefin) is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more, and is preferably 1.5 or less, more preferably 1.3 or less, even more preferably 1.1 or less, and even more preferably 0.9 or less. By setting it in such a range, the effects of the present invention tend to be more effectively exhibited.

[0058] <Inorganic fibers> The resin composition of the present embodiment may further contain 10.0 to 150.0 parts by mass of inorganic fibers per 100 parts by mass of the thermoplastic resin. By containing the inorganic fibers, the mechanical strength of the obtained resin molded article can be further improved. Examples of inorganic fibers include carbon fibers and glass fibers, and it is preferable to include glass fibers.

[0059] In the present embodiment, the inorganic fiber means a fibrous inorganic material, and more specifically, it is preferably a chopped shape in which 1,000 to 10,000 inorganic fibers are bundled and cut to a predetermined length. In the present embodiment, the inorganic fibers preferably have a number average fiber length of 0.5 to 10 mm, more preferably 1 to 5 mm. By using inorganic fibers with such a number average fiber length, the mechanical strength can be further improved. The number average fiber length is calculated from the measured value by randomly extracting inorganic fibers to be measured for the fiber length from an image obtained by observation with an optical microscope, measuring the long side of the fibers. The observation is performed at a magnification of 20 times, and the number of fibers measured is 1,000 or more. It roughly corresponds to the cut length. The cross section of the inorganic fiber may be any shape, such as a circle, an ellipse, an oval, a rectangle, a shape in which both short sides of a rectangle are joined by semicircles, a cocoon shape, etc., but a circle is preferable. Here, the circle includes not only a circle in the mathematical sense, but also what is usually called a circle in the technical field of this embodiment. The number average fiber diameter of the inorganic fibers is preferably 4.0 μm or more, more preferably 4.5 μm or more, and even more preferably 5.0 μm or more. The upper limit of the number average fiber diameter of the inorganic fibers is preferably 15.0 μm or less, and more preferably 12.0 μm or less. By using inorganic fibers having a number average fiber diameter in such a range, a resin molded product with excellent plating properties can be obtained even after wet heat. Furthermore, even if the resin molded product is stored for a long period of time or heat treated for a long period of time, high plating properties can be maintained. The number average fiber diameter of the inorganic fibers is calculated from the measured values ​​obtained by randomly extracting glass fibers to be measured for fiber diameter from an image obtained by observation with an electron microscope, measuring the fiber diameter near the center. The magnification of the observation is 1,000 times, and the number of fibers measured is 1,000 or more. The number average fiber diameter of glass fibers having a cross section other than a circle is the number average fiber diameter when converted into a circle having the same area as the cross section.

[0060] Next, the glass fiber preferably used in this embodiment will be described. The glass fibers used are fibers obtained by melt spinning commonly supplied glasses such as E-glass (Electrical glass), C-glass (Chemical glass), A-glass (Alkali glass), S-glass (High strength glass), D-glass, R-glass, and alkali-resistant glass. A preferred example of this embodiment is E-glass, and D-glass is also preferred to achieve a lower dielectric constant.

[0061] In order to lower the dielectric properties of the resin composition, the inorganic fibers in this embodiment are preferably low-dielectric inorganic fibers, and more preferably low-dielectric glass fibers. The term "low dielectric inorganic fiber" refers to an inorganic fiber having a low relative dielectric constant and dielectric loss tangent, and is exemplified by an inorganic fiber having a relative dielectric constant of 7 or less. The relative dielectric constant here is a value measured in accordance with ASTM D 150. An example of such low dielectric glass fiber is glass fiber made of 65-85% by mass of SiO2, 15-30% by mass of B2O3, 0-4% by mass of sodium oxide (Na2O) and / or potassium oxide (K2O), and 0-4% by mass of other components (the total amount here does not exceed 100% by mass, and preferably the total is 100% by mass). Glass fibers with a high amount of B2O3 are known as glass fibers with a low relative dielectric constant.

[0062] The glass fiber used in this embodiment is preferably surface-treated with a surface treatment agent such as a silane coupling agent, for example, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, etc. The amount of the surface treatment agent attached is preferably 0.01 to 1 mass% of the glass fiber. Furthermore, if necessary, it is also possible to use a glass fiber that has been surface-treated with a lubricant such as a fatty acid amide compound or silicone oil, an antistatic agent such as a quaternary ammonium salt, a resin having a film-forming ability such as an epoxy resin or urethane resin, or a mixture of a resin having a film-forming ability with a heat stabilizer, a flame retardant, etc.

[0063] The content of inorganic fibers (preferably glass fibers) in the resin composition of this embodiment is preferably 10.0 parts by mass or more, more preferably 20.0 parts by mass or more, even more preferably 30.0 parts by mass or more, and even more preferably 40.0 parts by mass or more, particularly 50.0 parts by mass or more, relative to 100 parts by mass of thermoplastic resin. By making it equal to or more than the lower limit, the mechanical strength of the obtained resin molded product tends to be further improved. In addition, the content of inorganic fibers (preferably glass fibers) in the resin composition of this embodiment is preferably 150.0 parts by mass or less, more preferably 120.0 parts by mass or less, even more preferably 100.0 parts by mass or less, even more preferably 80.0 parts by mass or less, and even more preferably 70.0 parts by mass or less, relative to 100 parts by mass of thermoplastic resin. By making it equal to or less than the upper limit, the dielectric properties of the resin composition tend to be lowered. In addition, the content of inorganic fibers (preferably glass fibers) in the resin composition of this embodiment is preferably 10.0 mass% or more in the resin composition, more preferably 15.0 mass% or more, and even more preferably 18.0 mass% or more. By making it equal to or more than the lower limit, the mechanical strength of the obtained resin molded product tends to be further improved. In addition, the content of inorganic fibers (preferably glass fibers) in the resin composition of this embodiment is preferably 50.0 mass% or less in the resin composition, more preferably 45.0 mass% or less, even more preferably 40.0 mass% or less, even more preferably 35.0 mass% or less, and even more preferably 34.0 mass% or less. By making it equal to or less than the upper limit, the dielectric properties of the resin composition tend to be lower. The resin composition of the present embodiment may contain only one type of inorganic fiber, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0064] <Talc> The resin composition of the present embodiment may further contain 0.1 to 200.0 parts by mass of talc relative to 100 parts by mass of the laser direct structuring additive. By containing talc, it is possible to improve the dimensional stability and the appearance of the product, and also to increase the plating growth rate. Furthermore, by containing talc, it is possible to improve the plating property of the resin molded product even if the content of the LDS additive is reduced. The talc may be surface-treated with at least one compound selected from polyorganohydrogensiloxanes and organopolysiloxanes. In this case, the amount of the siloxane compound attached to the talc is preferably 0.1 to 5% by mass of the talc. The number average particle size of talc is preferably 1 to 50 μm, and more preferably 2 to 25 μm. Talc is usually scaly, and the length of the longest part is taken as the average particle size. The number average particle size of talc is calculated from the measured values ​​obtained by randomly extracting talc particles to be measured for particle size from an image obtained by observation with an electron microscope, measuring the particle size of the sample, and then the number of particles is measured. The magnification of observation is 1,000 times, and the number of particles measured is 1,000 or more.

[0065] The content of talc in the resin composition of this embodiment is preferably 0.1 parts by mass or more, more preferably 1.0 parts by mass or more, even more preferably 10.0 parts by mass or more, even more preferably 60.0 parts by mass or more, and even more preferably 100.0 parts by mass or more, relative to 100.0 parts by mass of the laser direct structuring additive. By making it equal to or more than the lower limit, plating property tends to be further improved. In addition, the content of talc in the resin composition of this embodiment is preferably 200.0 parts by mass or less, more preferably 180.0 parts by mass or less, even more preferably 170.0 parts by mass or less, even more preferably 160.0 parts by mass or less, and even more preferably 150.0 parts by mass or less, relative to 100 parts by mass of the laser direct structuring additive. By making it equal to or less than the upper limit, the mechanical properties of the obtained molded product can be more effectively improved. In addition, when blended, the content of talc in the resin composition of this embodiment is preferably 0.1 part by mass or more, more preferably 1.0 part by mass or more, and even more preferably 4.5 parts by mass or more, relative to 100 parts by mass of the thermoplastic resin, and is preferably 20.0 parts by mass or less, more preferably 15.0 parts by mass or less, and even more preferably 12.0 parts by mass or less. The resin composition of the present embodiment may contain only one type of talc, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0066] <Release agent> The resin composition of the present embodiment may further contain a release agent. The release agent is mainly used to improve the productivity during molding of the resin composition. Examples of the release agent include aliphatic carboxylic acid amides, aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, and polysiloxane silicone oils.

[0067] For details about the release agent, reference can be made to the descriptions in paragraphs 0037 to 0042 of JP 2016-196563 A and paragraphs 0048 to 0058 of JP 2016-078318 A, the contents of which are incorporated herein by reference.

[0068] When the release agent is added, the lower limit of the content of the release agent is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and the upper limit is preferably 2.0% by mass or less, more preferably 1.5% by mass or less, based on the resin composition. By setting the content within such a range, the release property can be improved when molding using a mold such as injection molding, and mold contamination can be effectively suppressed. The release agent may be used alone or in combination of two or more kinds. When two or more kinds are used, the total amount is preferably within the above range.

[0069] <Other additives> The resin composition of the present embodiment may contain other components in addition to the above. Examples of other components include light stabilizers, heat stabilizers, alkalis, elastomers, titanium oxide, antioxidants, hydrolysis resistance improvers, matting agents, UV absorbers, nucleating agents, plasticizers, dispersants, antistatic agents, coloring inhibitors, gelling inhibitors, colorants, and flame retardants. For details of these, refer to paragraphs 0130 to 0155 of Japanese Patent No. 4894982, the contents of which are incorporated herein by reference. The total amount of these components is preferably 20% by mass or less of the resin composition. Each of these components may be used alone or in combination of two or more. In the resin composition of the present embodiment, the total amount of the thermoplastic resin, polyolefin, LDS additive, and, optionally, the inorganic fibers, release agent, and talc is preferably 95 mass % or more of the resin composition, more preferably 98 mass % or more, and even more preferably 99 mass % or more. In addition, the resin composition of the present embodiment preferably does not contain calcium copper titanate.

[0070] <Method of producing resin composition> As a method for producing the resin composition of the present embodiment, any method may be adopted. For example, a method in which a thermoplastic resin, a polyolefin, an LDS additive, inorganic fibers, etc. are mixed using a mixing means such as a V-type blender to prepare a lump-sum blend, which is then melt-kneaded in a vented extruder and pelletized. Alternatively, a two-stage kneading method in which components other than inorganic fibers are thoroughly mixed in advance, and then melt-kneaded in a vented extruder to produce pellets, the pellets are mixed with a reinforcing filler, and then melt-kneaded in a vented extruder is also included. Furthermore, a method can be mentioned in which components other than the inorganic fibers are thoroughly mixed in advance using a V-type blender or the like, and the mixture is fed from the first chute of a vented twin-screw extruder, while the inorganic fibers are fed from the second chute midway through the extruder, followed by melt-kneading and pelletization.

[0071] The screw configuration of the kneading zone of the extruder is preferably such that an element that promotes kneading is disposed on the upstream side and an element capable of increasing pressure is disposed on the downstream side. Examples of elements that promote kneading include a progressive kneading disc element, an orthogonal kneading disc element, a wide kneading disc element, and a progressive mixing screw element.

[0072] The heating temperature during melt kneading can usually be appropriately selected from the range of 180 to 360°C. If the temperature is too high, decomposition gas is likely to be generated, which may cause extrusion defects such as strand breakage. Therefore, it is desirable to select a screw configuration that takes into consideration shear heat generation, etc. In order to suppress decomposition during kneading and subsequent molding processes, it is desirable to use antioxidants and heat stabilizers.

[0073] <Physical properties of resin composition> The resin composition of the present embodiment preferably has low dielectric properties, and in particular, preferably has a low relative dielectric constant. For example, when the resin composition of the present embodiment is compared with a resin composition obtained by removing polyolefin from the resin composition of the present embodiment, if the resin composition of the present embodiment has a lower relative dielectric constant, it can be said that the dielectric constant is low. For example, the relative dielectric constant of the resin composition of this embodiment at a frequency of 2.45 GHz can be 3.60 or less, and can also be 3.50 or less. The lower limit of the relative dielectric constant is ideally 0, but the required performance is also satisfied even if it is, for example, 1.00 or more, or even 2.80 or more. In particular, it is preferable that the above range is satisfied when a polyamide resin is used as the thermoplastic resin. The resin composition of the present embodiment preferably has a low dielectric tangent. For example, the specific dielectric tangent at a frequency of 2.45 GHz of the resin composition of this embodiment can be 0.020 or less, and can also be 0.015 or less. The lower limit is ideally 0, but the required performance is satisfied even if it is, for example, 0.001 or more, or even 0.008 or more. In particular, it is preferable that the above range is satisfied when a polyamide resin is used as the thermoplastic resin.

[0074] The resin composition of the present embodiment has a bending strength of preferably 140 MPa or more, more preferably 145 MPa or more, and even more preferably 150 MPa or more, according to ISO 178, when molded to a thickness of 4 mm. The upper limit of the bending strength is not particularly set, but is practically, for example, 270 MPa or less, further 260 MPa or less, and particularly 250 MPa or less. In particular, it is preferable that the bending strength is within the above range when a polyamide resin is used as the thermoplastic resin. The resin composition of the present embodiment has a flexural modulus of 5.0 GPa or more, more preferably 5.5 GPa or more, and even more preferably 6.0 GPa or more, according to ISO178, when molded to a thickness of 4 mm. The upper limit of the flexural modulus is not particularly specified, but is practically, for example, 15 GPa or less, further 14 GPa or less, and particularly 13 GPa or less. In particular, it is preferable that the flexural modulus is within the above range when a polyamide resin is used as the thermoplastic resin.

[0075] The resin composition of this embodiment has a Charpy notched impact strength of 2 kJ / m when molded to a thickness of 4 mm, in accordance with the ISO 179 standard. 2 The upper limit of the notched Charpy impact strength is not particularly limited, but is preferably 15 kJ / m 2 The following is practical. In particular, when a polyamide resin is used as the thermoplastic resin, it is preferable that the above range is satisfied.

[0076] The above-mentioned relative dielectric constant, dielectric loss tangent, flexural strength, flexural modulus, and Charpy notched impact strength are each measured according to the method described in the Examples section below.

[0077] <Resin molded products> This embodiment also discloses a resin molded article formed from the resin composition of this embodiment. In the present embodiment, the manufacturing method of the resin molded product is not particularly limited, and any molding method generally used for resin compositions can be used. Examples of such molding methods include injection molding, ultra-high speed injection molding, injection compression molding, two-color molding, gas-assisted hollow molding, molding using a heat-insulating mold, molding using a rapid heating mold, foam molding (including supercritical fluid), insert molding, IMC (in-mold coating molding) molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, and blow molding. A molding method using a hot runner system can also be used.

[0078] The resin molded article formed from the resin composition of the present embodiment is preferably used as a resin molded article having a plating on the surface of the resin molded article. The plating in the resin molded article of the present embodiment is preferably an embodiment having an antenna performance.

[0079] <Method of manufacturing plated resin molded products> Next, a method for producing a plated resin molded article will be disclosed, which includes irradiating a laser onto the surface of a resin molded article formed from the resin composition of this embodiment, and then applying a metal to form plating. Fig. 1 is a schematic diagram showing a process of forming a plating on the surface of a resin molded product 1 by laser direct structuring technology. In Fig. 1, the resin molded product 1 is a flat substrate, but it does not necessarily have to be a flat substrate and may be a resin molded product with a curved surface partially or entirely. In addition, the obtained plated resin molded product is not limited to a final product, but is intended to include various parts.

[0080] Returning to FIG. 1 again, a resin molded article 1 is irradiated with a laser 2. The laser here is not particularly limited and can be appropriately selected from known lasers such as a YAG laser, an excimer laser, and an electromagnetic ray, with a YAG laser being preferred. The wavelength of the laser is also not particularly limited. A preferred wavelength range is 200 nm to 1200 nm, and more preferably 800 to 1200 nm. When the laser is irradiated, the resin molded article 1 is activated only at the portion 3 irradiated with the laser. In this activated state, the resin molded article 1 is applied to a plating liquid 4. The plating liquid 4 is not particularly specified, and a wide variety of known plating liquids can be used. A plating liquid (particularly, an electroless plating liquid) containing one or more of copper, nickel, silver, gold, and palladium as a metal component is preferable, a plating liquid (particularly, an electroless plating liquid) containing one or more of copper, nickel, silver, and gold is more preferable, and a plating liquid (particularly, an electroless plating liquid) containing copper is even more preferable. That is, in the plating of this embodiment, the metal component is preferably at least one of the above metals. The method for applying the resin molded article 1 to the plating liquid 4 is not particularly limited, but an example is a method of immersing the resin molded article in a liquid containing the plating liquid. After the plating liquid is applied to the resin molded article, plating 5 is formed only on the portions irradiated with the laser. In the method of this embodiment, it is possible to form a plating (circuit) having a gap of 1 mm or less, or even 150 μm or less (the lower limit is not particularly specified, but for example, 30 μm or more). In order to prevent corrosion or deterioration of the formed plating (circuit), the plating can be further protected with nickel or gold, for example, after electroless plating. Similarly, it is also possible to form a required film thickness in a short time by using electrolytic plating after electroless plating. The above-mentioned method for producing a plated resin molded product is also preferably used as a method for producing a portable electronic device part having an antenna, including the above-mentioned method for producing a plated resin molded product.

[0081] The resin molded article obtained from the resin composition of the present embodiment can be used for various applications, such as electronic components such as sensors, connectors, switches, relays, conductive circuits, and antennas (particularly, portable electronic device components, communication base stations, and personal computer peripherals).

[0082] In addition, the descriptions in JP 2011-219620 A, JP 2011-195820 A, JP 2011-178873 A, JP 2011-168705 A, and JP 2011-148267 A can be referred to without departing from the spirit of this embodiment. EXAMPLES

[0083] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.

[0084] In this example, the following raw materials were used: [Table 1]

[0085] In Table 1 above, MAH stands for maleic anhydride, HDPE stands for high density polyethylene, PP stands for polypropylene, LDPE stands for low density polyethylene, PTFE stands for polytetrafluoroethylene, and PPS stands for polyphenylene sulfide.

[0086] Examples 1 to 10, Comparative Examples 1 to 4 <Compound> Each component was weighed out so as to obtain the composition shown in Tables 2 to 4 below (each component in Tables 2 to 4 is in parts by mass), and the components except for the inorganic fiber (glass fiber) were blended in a tumbler and fed into a twin-screw extruder (Shibaura Machine Co., Ltd., TEM26SS) from the base. After melting, the inorganic fiber (glass fiber) was side-fed to produce a resin composition (pellets). The temperature of the twin-screw extruder was set to 300°C. Each component in Tables 2 to 4 is shown in mass ratio.

[0087] <Flexural strength and flexural modulus> The pellets obtained by the above manufacturing method were dried at 120°C for 4 hours, and then injection molded into ISO tensile test specimens (4 mm thick) using an injection molding machine (manufactured by Shibaura Machine Co., Ltd., "EC75SX") under conditions of a cylinder temperature of 300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds. The flexural strength (unit: MPa) and flexural modulus (unit: GPa) were measured at a temperature of 23°C in accordance with ISO178.

[0088] <Notched Charpy impact strength> The pellets obtained by the above manufacturing method were dried at 120°C for 4 hours, and then injection molded into ISO tensile test specimens (4 mm thick) using an injection molding machine (manufactured by Shibaura Machine Co., Ltd., "EC75SX") under conditions of a cylinder temperature of 300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds. Using the ISO tensile test pieces (4 mm thick) obtained above, Charpy impact strength (notched) was measured at a temperature of 23° C. in accordance with the ISO179 standard. The unit is kJ / m 2 As shown in.

[0089] <Deflection temperature under load (DTUL)> The pellets obtained by the above manufacturing method were dried at 120°C for 4 hours, and then injection molded into ISO multipurpose test pieces (4 mm thick) using an injection molding machine (manufactured by Shibaura Machine Co., Ltd., "EC75SX") under conditions of a cylinder temperature of 300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds. The ISO multipurpose test piece (4 mm thick) obtained above was processed into a shape based on ISO75-1 and ISO75-2, and the deflection temperature under load (unit: °C) was measured at a load of 1.80 MPa based on ISO75-1 and ISO75-2.

[0090] <Dielectric constant / dielectric tangent> The relative dielectric constant and the dielectric loss tangent were measured at a frequency of 2.45 GHz by a cavity resonator perturbation method using a 100 mm×100 mm×2 mm flat plate specimen formed from the resin composition. Specifically, the pellets obtained by the above manufacturing method were dried at 120°C for 4 hours, and then injection molded in an injection molding machine (Shibaura Machine Co., Ltd., "EC75SX") under conditions of a cylinder temperature of 300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds to mold flat test pieces of 100 mm x 100 mm x 2 mm. From the obtained flat test piece, a flat test piece of 100 mm x 1 mm x 2 mm was obtained by cutting in the longitudinal direction of the flow direction, and the relative dielectric constant and dielectric loss tangent at a set frequency were measured by a cavity resonator perturbation method. For the measurement, a network analyzer manufactured by KEYSIGHT and a cavity resonator manufactured by Kanto Electronics Application Development Co., Ltd. were used.

[0091] <Plating ability> A 10 x 10 mm area of ​​the ISO multipurpose test piece (4 mm thick) obtained above was irradiated with a Trumpf VMc1 laser irradiation device (1064 nm wavelength YAG laser maximum output 15 W) at a power of 10 W, a frequency of 80 kHz, and a speed of 2 m / s. The subsequent plating process involved treatment for 10 minutes in a 65°C plating bath (set temperature 68°C) of a MacDermid Copper100XB electroless plating device. A: Plating was formed B: No plating was formed

[0092] [Table 2] [Table 3] [Table 4]

[0093] As is clear from the above results, the resin compositions of the present invention were able to achieve low dielectric properties, in particular a low relative dielectric constant, while maintaining plating properties (Examples 1 to 10). In contrast, when no polyolefin was blended (Comparative Example 1), the relative dielectric constant did not decrease.Also, when a resin other than polyolefin was alloyed (Comparative Examples 2 and 3), the relative dielectric constant did not decrease. On the other hand, when the LDS additive was not added (Comparative Example 4), the relative dielectric constant was low, but plating could not be formed. [Explanation of symbols]

[0094] 1 Resin molded products 2. Laser 3 Laser irradiated area 4. Plating solution 5. Plating

Claims

1. A thermoplastic resin; Laser direct structuring additives; and a polyolefin, The thermoplastic resin includes at least one of a polycarbonate resin, a polyphenylene ether resin, a polyester resin, and a polyamide resin; The thermoplastic resin contains 4.0 to 30.0 parts by mass of polyolefin relative to 100 parts by mass of the thermoplastic resin, The mass ratio of the polyolefin to the laser direct structuring additive (laser direct structuring additive / polyolefin) is 0.1 or more and 1.3 or less; The polyolefin is an acid-modified polyolefin obtained by modifying a homopolymer and / or copolymer of an olefin selected from the group consisting of ethylene, propylene, and butene with maleic anhydride. Low dielectric resin composition for laser direct structuring.

2. The resin composition according to claim 1 , wherein the thermoplastic resin comprises a polyamide resin.

3. The resin composition according to claim 2 , wherein the polyamide resin comprises a semi-aromatic polyamide resin.

4. The resin composition according to claim 2, wherein at least one of the polyamide resins contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, 70 mol % or more of the diamine-derived structural unit is derived from xylylenediamine, and 70 mol % or more of the dicarboxylic acid-derived structural unit is derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 20 carbon atoms.

5. The resin composition according to any one of claims 1 to 4, comprising 1.0 to 30.0 parts by mass of the laser direct structuring additive relative to 100 parts by mass of the thermoplastic resin.

6. The resin composition according to any one of claims 1 to 5, wherein the laser direct structuring additive comprises at least one of copper, antimony, tin, aluminum and zinc.

7. The resin composition according to any one of claims 1 to 5, wherein the laser direct structuring additive comprises copper chromium copper oxide and / or an oxide containing antimony and tin.

8. The resistivity of the laser direct structuring additive is 5×10 3 The resin composition according to any one of claims 1 to 7, having a modulus of more than Ω cm.

9. The resin composition according to any one of claims 1 to 8, further comprising 10.0 to 150.0 parts by mass of inorganic fibers per 100 parts by mass of the thermoplastic resin.

10. The resin composition according to claim 9 , wherein the inorganic fibers have a relative dielectric constant of 7 or less.

11. The resin composition according to claim 9 or 10, wherein the inorganic fibers include glass fibers.

12. The glass fiber is 65 to 85 mass % of SiO 2 and 15 to 30 mass% B 2 O 3 and 0 to 4 mass% sodium oxide (Na 2 O) and / or potassium oxide (K 2 O) and 0 to 4 mass% of other components. The resin composition according to claim 11.

13. The resin composition according to any one of claims 9 to 12, wherein the inorganic fibers are contained in an amount of 20.0 to 80.0 parts by mass per 100 parts by mass of the thermoplastic resin.

14. The resin composition according to any one of claims 1 to 13, further comprising 0.1 to 200.0 parts by mass of talc per 100.0 parts by mass of the laser direct structuring additive.

15. The resin composition according to any one of claims 1 to 14, wherein the resin composition has a relative dielectric constant of 3.60 or less at a frequency of 2.45 GHz.

16. A resin molded product formed from the resin composition according to any one of claims 1 to 15.

17. The resin molded article according to claim 16, wherein the surface of the resin molded article is plated.

18. The resin molded product according to claim 17, wherein the plating has a function as an antenna.

19. The resin molded article according to any one of claims 16 to 18, which is a portable electronic device part.

20. A method for producing a plated resin molded product, comprising: irradiating a surface of a resin molded product formed from the resin composition according to any one of claims 1 to 15 with a laser, and then applying a metal to form a plating.

Citation Information

Patent Citations

  • Modified resin composition and preparation method and application thereof

    CN102643535A

  • Thermoplastic resin composition, resin molding, and process for producing resin molding having plating layer attached thereto

    JP2013144767A

  • Polyamide molding material and use thereof

    JP2014043549A

  • Pellet, method of producing pellet, resin molding, and method of producing resin molding with plated layer

    JP2015218323A

  • Fiber-reinforced polymer composition

    JP2020515659A